Wearing surgical masks does not affect heart rate and blood lactate accumulation during cycle ergometer exercise - Boldrini, L.; Danelon, F.; Fusetti, D.; Lucenteforte, G.; Roi, G. S. (The Journal of Sports Medicine and Physical Fitness, 2020)
LETTERS TO THE EDITOR The pandemic emergency of COVID-19 has dramatically affected our lives leading to a change of daily habits. Most worldwide gov-emments directions to prevent virus diffusion in the community include the use of face masks. These devices act as a barrier to droplets produced during breathing and speaking, mandatory in-door but also outdoor in conditions where social distancing is not possible. The World Health Organization (WHO) recommends the use of surgical masks as a way to prevent virus diffusion, together with hygiene measures and social distancing.